• tile-compare Funktion
  • tilecompare
  • 11.01.2021
Um die Lizenzinformationen zu sehen, klicken Sie bitte den gewünschten Inhalt an.
  • Ohne Hintergrund

    f(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+2x+1
    g(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} g(x) = x^2
    h(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} h(x) = 6x^{23} (x^3+2)
    k(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} k(x) = (3^3+5x)^3
    l(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} l(x) = 3*x + 78
    m(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} m(x) = 3*x / 3x^9
    n(x)=x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} n(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
    o(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} o(x) = x^2+2x+1
    p(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} p(x) = x^2
    q(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} q(x) = 6x^{23} (x^3+2)
    r(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} r(x) = (3^3+5x)^3
    s(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} s(x) = 3*x + 78
    t(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} t(x) = 3*x / 3x^9
    u(x)=x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} u(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
    v(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} v(x) = x^2+2x+1
    w(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} w(x) = x^2
    a(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} a(x) = 6x^{23} (x^3+2)
    b(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} b(x) = (3^3+5x)^3
    c(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} c(x) = 3*x + 78
    d(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} d(x) = 3*x / 3x^9
    e(x)=x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} e(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
    i(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} i(x) = x^2+2x+1
    j(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} j(x) = x^2
    z(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} z(x) = 6x^{23} (x^3+2)
    f(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = (3^3+5x)^3
    f(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x + 78
    f(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x / 3x^9
    f(x)=x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
  • Mit Hintergrund

    f(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+2x+1
    f(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2
    f(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 6x^{23} (x^3+2)
    f(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = (3^3+5x)^3
    f(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x + 78
    f(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x / 3x^9
    f(x)=x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
    f(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+2x+1
    f(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2
    f(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 6x^{23} (x^3+2)
    f(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = (3^3+5x)^3
    f(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x + 78
    f(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x / 3x^9
    f(x)=x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
    f(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+2x+1
    f(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2
    f(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 6x^{23} (x^3+2)
    f(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = (3^3+5x)^3
    f(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x + 78
    f(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x / 3x^9
    f(x)=x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2
    f(x)=x2+2x+1\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+2x+1
    f(x)=x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2
    f(x)=6x23(x3+2)\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 6x^{23} (x^3+2)
    f(x)=(33+5x)3\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = (3^3+5x)^3
    f(x)=3x+78\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x + 78
    f(x)=3x/3x9\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = 3*x / 3x^9
    f(x)=x2+x2+x2+x2+x2+x2+x2+x2\gdef\cloze#1{\colorbox{none}{\color{transparent}{\large{$\displaystyle #1$}}}} f(x) = x^2+x^2+x^2+x^2+x^2+x^2+x^2+x^2